Impact of seasonality, redox conditions, travel distances and initial concentrations on micropollutant removal during riverbank filtration at four sites. (July 2020) - Oberleitner, Daniela; Schulz, Wolfgang; Bergmann, Axel; Achten, Christine
Abstract: Riverbank filtration (RBF) is a reliable water purification technique that has proven to be suitable for the removal of organic micropollutants. Its removal efficiency and dependency on a variety of factors such as redox conditions, temperatures, geology, travel times, level of initial micropollutant concentrations and seasonality were investigated during three seasonal sampling campaigns. Two anoxic (silty sand, Ems river) and two oxic (gravel, Ruhr river) RBF sites in Germany with different travel distances (42–633 m) were studied. Micropollutant concentrations were examined using a large-volume direct injection liquid chromatography method coupled to high-resolution mass spectrometry. Seasonal differences in micropollutant concentrations in the rivers were observed for chlorotolurone, diclofenac, terbuthylazine, mecoprop-P, MCPA (2-methyl-4-chlorophenoxyacetic acid) and propyphenazone. Redox dependencies in RBF were only found for sulfamethoxazole, propyphenazone, terbuthylazine and carbamazepine. Data for oxazepam, tramadol, N-desmethyl-tramadol, tilidin-desmethyl, carbamazepine and carbendazim indicate a required minimum travel distance of e.g. 100–200 m for the complete removal. Notably, travel time did not seem to be a substantial factor for their removal. High conductivity aquifers are also well suited for micropollutant removal. Seasonal initial concentration level variations showed no impact on the resulting abstraction well concentrations. Although the calculated removal efficiencies varied, they proved to be improper for seasonal raw water quality comparison. Knowledge of micropollutant behavior in riverbank filtration was broadened and RBF proved to be well suited for effective micropollutant reduction throughout the year, yet for a complete removal long travel distances or further technical purification steps are required. Graphical abstract: Image 1 Highlights: Seasonal variations due to agricultural/medical use and degradation variabilities. Anoxic redox conditions supportive for degradation of some micropollutants. Data indicate minimum required travel distance rather than minimum travel time. Level of initial concentrations crucial for several removals during bank filtration.